Status of research on the application of melatonin in insomnia based on bibliometric visualization analysis and development trends - Liu, Huiying; Zhao, Jinying; Wang, Zhongke; Chen, Lu; Xie, Yuhong; Yang, Ning; Wang, Ying; Zheng, Peng; Wang, Fuchun (Frontiers in Psychiatry, 2025)
ObjectiveInsomnia has long been a public health challenge, severely affecting human quality of life. Circadian rhythms are regulated in part by melatonin, and exogenous melatonin has significant therapeutic promise. This study examines global research trends, collaborative networks, and theme evolution in the field of melatonin and insomnia research from 2015 to 2024 using bibliometric visualization techniques.MethodUsing the terms “melatonin” and “insomnia” (as well as their synonyms in the Medical Subject Headings (MeSH) database), this article looked for pertinent literature in the Web of Science Core Collection and PubMed databases. Articles published between January 1, 2015, and December 31, 2024, were included in the search. VOSviewer (version 1.6.20) was used to visualize countries, institutions, journals, and authors; Citespace (version 6.3 R1) was used to visualize keywords and references.ResultsThe two databases yielded 1,818 papers in total, of which 1,084 were included following screening. Even though there are annual variations, the general trend is upward. The institutions and nations with the most publications among them are Harvard Medical School and the United States. The author with the most publications is Bruni O. The most significant co-citation frequency is found in Morin C.M. Among the cited references, Gringas P. (2017) has the most citations. Frontiers in Psychiatry and Sleep Medicine are the journals with the most publications.ConclusionMelatonin has been used mainly to treat insomnia in children, the elderly, and people with neurological disorders during the last ten years. Further, a trend for future research in this area is the convergence of insomnia with comorbidities like neurological disorders, cancer, and pain medication.